PENGARUH PELATIHAN KERJA TERHADAP KINERJA KARYAWAN J & T MEDAN - Rikawati Ginting Munthe (JURNAL REGIONOMIC, 2021)
The purpose of this study was to determine the effect of job training on employeeperformance at J&T Medan. In this study the population is all employees of J & T MedanRingroad Branch with a total of 35 people. The number of population is small, so thedetermination of the sample is done with a saturated sample (census sample), where allthe population is used as a sample. The independent variable in this study is job training,while the dependent variable is employee performance. Data analysis using simple linearregression analysis with the results of job training research has a positive and significanteffect on employee performance at J&T Express Medan with a significance value of tcountof 6.977 greater than t-table (1.691).